2009
DOI: 10.1016/j.ahj.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants with the metabolic syndrome in 20,806 white women: The women's health genome study

Abstract: Background-candidate genes associated with cardiovascular disease (CVD) represent potential risk factors for the metabolic syndrome (MetS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
(51 reference statements)
1
7
0
1
Order By: Relevance
“…For example, hypercholesterolemia may upregulate AGTR1 expression, shown in vascular smooth muscle cells. 37 Some studies have suggested that the AGTR1 A1166C polymorphism may predict incident or prevalent metabolic syndrome, 14,38 which is consistent with our hypertension results.…”
Section: Discussionsupporting
confidence: 89%
“…For example, hypercholesterolemia may upregulate AGTR1 expression, shown in vascular smooth muscle cells. 37 Some studies have suggested that the AGTR1 A1166C polymorphism may predict incident or prevalent metabolic syndrome, 14,38 which is consistent with our hypertension results.…”
Section: Discussionsupporting
confidence: 89%
“…APOA1 gene polymorphisms (rs2727784) are well known to disturb lipid metabolism (8,26), and the current study suggests that such polymorphisms may also influence the consistency of this disturbance across eating occasions. The IL-1 pathway is an important mediator of inflammatory reactions with polymorphisms rs1800587 and rs1143634, which are implicated in the development of obesity and metabolic disarray (38)(39)(40). The current analysis also found that SNPs in genes encoding Toll-like receptor 4 (rs4986790, rs4986791) affected the reproducibility of response to an acute high fat intake.…”
Section: Discussionmentioning
confidence: 53%
“…There are only few studies that prospectively investigated C5 rs17611 on outcome [8,20,21], and so far, gender aspects of C5 rs17611 have not been satisfactory investigated. Interestingly, data from The Women’s Health Genome Study showed that the C5 rs17611 SNP is associated with a decreased risk for the development of the metabolic syndrome even though male patients were not investigated [22]. To our knowledge, our study is the first that observed a gender‐related association between C5 rs17611 and the occurrence of future MACE.…”
Section: Discussionmentioning
confidence: 91%